How to Develop Visual Representation Test Instruments on Optical Equipment Material for High School Students? - Nurmahasih, Utari; Istiyono, Edi; Sadly, Deni; Warjo, Warjo (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
In physics learning, visual representation is an important tool for turning abstract concepts into more easily understood ones, especially topics about optical equipment. However, current teaching instruments are often less effective in providing adequate visualization. This research on the development of visual representation test instruments for senior high school or Islamic senior high school (SMA/MA) on optical device topic was carried out with the aims of 1) developing a visual representation test instrument on optical devices material, 2) determining the expert validity of the visual representation instrument on optical devices material, 3) determine the item validity and reliability of the visual representation instrument on optical devices material through limited trials, 4) determine the level of difficulty and differentiability of visual representation instruments on optical devices material. This research design was the Research and Development procedure from Borg and Gall, which was modified up to the product trial stage. Data was collected from the expert validation and product trials and then analyzed using a quantitative description. Eight validators validated the visual representation instrument. The research subjects were 30 eleventh-grade science students. The results of the analysis concluded that the product was suitable for use by teachers in assessing student representation. Therefore, the visual representation test instrument for optical devices material is suitable for teachers. Through this instrument, it is hoped that we can see the ability of students' representation instruments in learning optics.